Application of Chiral Piperidine Scaffolds in Drug Design - Qiu-Shi Chen; Jian-Qi Li; Qing-Wei Zhang (Georg Thieme Verlag KG, 2023)
Abstract Chiral piperidine scaffolds are prevalent as the common cores of a large number of active pharmaceuticals in medical chemistry. This review outlined the diversity of chiral piperidine scaffolds in recently approved drugs, and also covers the scaffolds in leads and drug candidates. The significance of chiral piperidine scaffolds in drug design is also discussed in this article. With the introduction of chiral piperidine scaffolds into small molecules, the exploration of drug-like molecules can be benefitted from the following aspect: (1) modulating the physicochemical properties; (2) enhancing the biological activities and selectivity; (3) improving pharmacokinetic properties; and (4) reducing the cardiac hERG toxicity. Given above, chiral piperidine-based discovery of small molecules will be a promising strategy to enrich our molecules' library to fight against diseases.